PENATAAN URGENSI INFORMASI DALAM MAJALAH ANAK - Tarti Khusnul Khotimah (Balai Bahasa Provinsi Papua, 2019)
This research discusses about the ordering of information urgency in children magazine. The information urgency is related to important (theme) information and not important (rheme) information. The ordering of information was discussed consist of method and form in its ordering. The method of this researh are listen method with written technique and apportion method with BUL and read sign method. Data was collected from the discourse in Indonesian children magazine Bobo, Kreatif, Potret Negeriku, and Aku Anak Saleh. The result of this research was found the ordering of information urgency in children magazine can do by theme holding, thematics, theme changing, and dethematics. The form on its ordering consist of showing, changing, losing, and repeating.